Corrosion behavior of welded joints in ozonated acidic solution - Татарченко, Галина Олеговна (Eastern-European Journal of Enterprise Technologies, 2014)
The corrosion-electrochemical behavior of welded joints of steels and alloys, used as instrumental for organic synthesis processes in the presence of ozone was investigated. It was determined that welded joints in ozonated media are characterized by the increase in anodic current densities in the whole range of potentials and the shift of Еcor more negatively compared with the base metal that is associated with the decrease in active centers, on which ozone can be reduced. In ozone synthesis conditions, the alloy 06ХН28НДТ can be recommended as a structural material for reactors manufacture. In the ozone oxidation processes, it is necessary to pay attention to welded joints, especially for stainless steels such as "18-10" as wide "cathodic loop" formation on polarization curves indicates their tendency to intergranular corrosion (IGC). Corrosion can also proceed in dangerous areas of pitting formation and repassivation of steels under the ozone action. Welded joints of ferritic stainless steels 08Х17Т show the tendency to IGC in periodical ozone syntheses that precludes the possibility of using welding sets or requires protection of joint.